Feeding ecology and diet of the southern geladas (Theropithecus gelada obscurus) in human‐modified landscape, Wollo, Ethiopia. Issue 16 (22nd July 2021) - Kifle, Zewdu; Bekele, Afework
Abstract: Studying the dietary flexibility of primates that live in human‐modified environments is crucial for understanding their ecological adaptations as well as developing management and conservation plans. Southern gelada ( Theropithecus gelada obscurus ) is an endemic little‐known subspecies of gelada that inhabits human‐modified landscapes in the northern central highlands of Ethiopia. During an 18‐month period, we conducted this intensive study in an unprotected area of a human‐modified landscape at Kosheme in Wollo to investigate the feeding ecology of southern geladas and their dietary responses to seasonal variations. We quantified the monthly and seasonal diet data from a band of southern geladas using instantaneous scan sampling method at 15‐min intervals, and green grass phenology and availability using visual inspection from the randomly selected permanent plots. The overall average diet of southern geladas at Kosheme constituted grass blades 55.4%, grass undergrounds 13.2%, grass bulbs 5.6%, grass seeds 5.4%, herb leaves 4.0, fruits 7.3%, and cereal crops 5.6%. Grass blade consumption increased with increasing green grass availability, while underground food consumption increased with decreasing green grass availability, and vice versa. Southern geladas spent significantly more time feeding on the grass blades and herb leaves and significantly less time on bulbs during the wet season than the dry season. Underground grass items (rhizomes and corms) were not consumed during the wet season, but made up 22.3% of the dry season diet. Thus, although grass blades are staple diet items for geladas, underground diet items are important "fallback foods" at Kosheme. Our result shows insights into the dietary flexibility southern geladas adopt to cope with human‐modified landscapes of the north‐central Ethiopian Highlands. Thus, the study contributes to a better understanding of how changing environments shape primate ecology and evolution. Abstract : Studying the dietary flexibility of primates that live in human‐modified environment is crucial for understanding ecological adaptations. We conducted this intensive study in an unprotected area of human‐modified landscape to investigate the dietary responses of southern geladas to human disturbances and seasonal variations. The study contributes to a better understanding of how changing environments shape primate ecology and evolution.